Persistance of gender wage inequality - Short, Christine; Nowak, Margaret (Sage Publications Ltd., 2009)
Qualitative research on the perceptions of industrial relations stakeholders of the persistence of gender wage inequality during the period 1990 to 2003 is reported. During this period the gap between the average weekly ordinary time earnings of women and men working full time in Australia decreased by only one and a half percentage points, from 17 percent in 1990, to 15.5 percent in 2003 and the gap in Western Australia widened by 5 percentage points. Interviewees and the literature indicated that gender wage inequality was greatest within occupations whilst also occurring between occupations. Stakeholders interviewed felt that gender-related social/cultural values pervade the formal system of industrial relations as well as the wider society. These social/cultural values, changing slower than economic and industrial relations factors, result in persistent gender wage inequality as these values affect occupational choice before the market, the availability of jobs and training in the market and thus wages. Stakeholders showed that they believed that their gender-related values affected actions taken to, and decisions made in, industrial tribunals. Remedies for gender wage inequality thus must address not only action within the formal industrial relations system, but also perceptions and values in the wider society.